Strong Tribocatalytic Nitrogen Fixation of Graphite Carbon Nitride g-C3N4 through Harvesting Friction Energy - Zheng Wu; Taosheng Xu; Lujie Ruan; Jingfei Guan; Shihua Huang; Xiaoping Dong; Huamei Li; Yanmin Jia (Nanomaterials, 2022)
Mechanical energy derived from friction is a kind of clean energy which is ubiquitous in nature. In this research, two-dimensional graphite carbon nitride (g-C3N4) is successfully applied to the conversion of nitrogen (N2) fixation through collecting the mechanical energy generated from the friction between a g-C3N4 catalyst and a stirring rod. At the stirring speed of 1000 r/min, the tribocatalytic ammonia radical (NH4+) generation rate of g-C3N4 can achieve 100.56 μmol·L−1·g−1·h−1 using methanol as a positive charge scavenger, which is 3.91 times higher than that without any scavengers. Meanwhile, ammonia is not generated without a catalyst or contact between the g-C3N4 catalyst and the stirring rod. The tribocatalytic effect originates from the friction between the g-C3N4 catalyst and the stirring rod which results in the charges transfer crossing the contact interface, then the positive and negative charges remain on the catalyst and the stirring rod respectively, which can further react with the substance dissolved in the reaction solution to achieve the conversion of N2 to ammonia. The effects of number and stirring speed of the rods on the performance of g-C3N4 tribocatalytic N2 fixation are further investigated. This excellent and efficient tribocatalysis can provide a potential avenue towards harvesting the mechanical energy in a natural environment.